Assessing the potential role of arbuscular mycorrhizal fungi in improving the phytochemical content and antioxidant properties in Gomphrena globosa - Dhalaria, Rajni; Verma, Rachna; Sharma, Rohit; Jomova, Klaudia; Nepovimova, Eugenie; Kumar, Harsh; Kuca, Kamil (Scientific reports, 2024)
Strategies to increase the secondary metabolite production, obtained from medicinal plants has been the topic of research in recent years. The symbiotic interaction between arbuscular mycorrhizal fungi and plants allows host-fungus pairings to enhance secondary metabolite synthesis. Therefore, the current study investigated the effect of inoculating two distinct AMF species discretely as well as in conjunction on the flower-derived secondary metabolites in Gomphrena globosa. The findings showed that the plants inoculated with combined treatment exhibited higher total phenolic (50.11 mg GAE/g DW), flavonoids (29.67 mg QE/g DW), saponins (122.55 mg DE/g DW), tannins (165.71 TAE/g DW) and terpenoid (8.24 mg LE/g DW) content in the methanolic extract. HPTLC examination showed the existence of kaempferol and benzoic acid with the highest amount (0.90% and 5.83% respectively) observed in the same treatment. FTIR analysis revealed functional group peaks with increased peak intensity in the combination treatment. Higher antioxidant activities such as DPPH (IC50: 401.39 µg/mL), ABTS (IC50: 71.18 µg/mL) and FRAP (8774.73 µM Fe (II) equivalent) were observed in the methanolic extract of combined treatment. To our knowledge, this is the first study on the impact of AMF inoculation on bioactive compounds and antioxidant activities in G. globosa flowers. Moreover, this study could lead to the development of novel pharmaceuticals and herbal remedies for various diseases.
Keywords: Tannins; fenoly; Mycorrhizae; symbióza; Symbiotic interaction; Phytochemicals; Nutrient uptake; Arbuscular mycorrhizal fungi; Phenols; flavonoidy; rostlinné extrakty; antioxidancia; Antioxidant potential; Symbiosis; mykorhiza; Phytoconstituents; Gomphrena globosa; Flowers; taniny; saponiny; Saponins; Plant Extracts; květy; fytonutrienty; Flavonoids; Antioxidants